Influence of Prophylactic Ankle Bracing on Knee Joint Moments and Ground Reaction Forces during Side-step Cutting Tasks - Hyung Suk Yang; Rhonda Boros; Nida Roncesvalles; Yoonjung Park (Asian Society of Kinesiology, 2024)
OBJECTIVES Prophylactic ankle bracing is widely used to prevent ankle sprains, but its effects on knee joint mechanics, particularly regarding ACL injury risk, are less understood. This study aimed to investigate the influence of ankle bracing on knee joint kinetics and ground reaction forces (GRFs) during a 90° side-step cutting task. METHODS Thirty physically active participants (15 males, 15 females) performed cutting trials under braced and unbraced conditions. Knee flexion, abduction, and internal rotation moments, along with mediolateral, anteroposterior, and vertical GRFs, were measured using a motion analysis system and a force plate. Paired t tests were conducted to compare the knee joint moments and GRFs between the two conditions. RESULTS The results showed that while ankle bracing did not significantly affect GRFs, it significantly increased knee internal rotation moment (p = 0.003). No significant differences were observed in knee flexion or abduction moments. CONCLUSIONS Ankle bracing, though beneficial for ankle stability, may elevate the risk of ACL injuries during dynamic activities like cutting by increasing knee internal rotation moments. Clinicians and coaches should weigh the benefits of ankle bracing against potential risks to knee health and consider alternative injury prevention strategies focused on neuromuscular control and strength training.